Comparative Analysis of Arabic Textbook Tsanawi Grade 6 Mathayom with Al-Ashri Class 12 in Perspectives of the National Education Standards Agency in Aspects: Feasibility of Content, Language, Presentation and Graphic: Analisis Perbandingan Buku Teks Bahasa Arab Tsanawi Kelas 6 Mathayom Dengan Al - Ashri Kelas 12 Dalam Perspektif Badan Standar Nasional Pendidikan Dalam Aspek: Kelayakan Isi, Bahasa, Penyajian dan Kegrafikan - Risang Mahatmono; Najih Anwar (Indonesian Journal of Education Methods Development, 2020)
Textbooks are the basic foundation at all levels of education which play an important role in the learning process. Which contains learning material with good content standards. This study aims to determine and compare the quality of Arabic textbooks "Tsanawi" for grade 6 Mathayom and "Al-Ashri" grade 12. This textbook is analyzed for quality from the BSNP perspective in terms of content, language, presentation and graphic characteristics of the instrument components that are applicable to both books. In the preparation of this study, researchers used a method of content analysis conducted systematically, objectively, and using data calculation methods that were interpreted into qualitative data. The results of the research conducted are that the Arabic textbooks Al-Ashri and Tsanawi each have different advantages.